Echocardiographic diagnosis of sinus Valsalva aneurysm rupture in two pediatric patients - (:unkn) unknown (TURKISH J PEDIATRICS, 1999)
Sinus Valsalva aneurysm rupture (SVAR) is a rare cardiac abnormality that requires surgical correction when diagnosed. previously, cardiac catheterization and angiography were thought to be necessary for its diagnosis. We present two pediatric cases of SVAR with subarterial ventricular septal defect (VSD) diagnosed noninvasively by echocardiography; surgical findings confirmed the diagnosis. In both of our cases the origin of SVAR was the right coronary sinus. The first case was ruptured into the right ventricular cavity; the second was ruptured into the right ventricular outflow tract, Continuous murmurs heard during follow-up of children with VSD must alert the physician to this pathology. Combined two-dimensional, Doppler and color-Doppler echocardiography is an accurate, noninvasive method for diagnosis of SVAR.
Keywords: sinus of Valsava aneurysm rupture; echocardiography; subarterial ventricular septal defect; children; VENTRICULAR SEPTAL-DEFECT; FISTULA